THEORETICAL FRAMEWORK ON ROLE OF POLITICAL PARTIES IN GOVERNANCE (International Journal of Food and Nutritional Sciences, 2023)
The data has been taken from the existing statistical data prepared after interviewing confident party leaders, who will then have their remarks and answers to the questionnaire examined and included into the article. The data, facts, and statistics included in the thesis are drawn from secondary sources. The statistics from the Parliamentary speeches, the data that was collected by the CSDS (National Centre för the Research and Analysis of Changing Economies) statistics Unit, and the replies of the provincial political party executives provided in their responses to the survey are among the key resources for the information. Secondary sources include written works such as documents, articles that have been peer-reviewed, and media and magazine pieces.